The Influence of the Implementation of the Jigsaw Cooperative Guided Inquiry Learning Model on the Science Process Skills of Junior High School Students in Banda Aceh - Nurul Akmal; Ibrahim; Rubiah; Lismarita; Cut Morina Zubainur (Postgraduate, University of Mataram, 2025)
The purpose and objectives of this study were to determine the effect of the cooperative jigsaw guided inquiry learning model and the effect on students' learning achievement abilities and the correlation between the learning model and the initial abilities of junior high school students. The research design used was a posttest only control design with factorial. Data collection techniques used documentation in the form of students' initial achievement abilities, observation sheets and science process skills tests to measure their learning achievement. The results showed that the average score of the science process skills of the experimental class students was higher, namely 83.30 compared to the control class, namely 75.15. While the average score of the science process skills of students with high, medium, and low initial achievement abilities were 85.10, 81.15, and 76.20, respectively. The results of the data analysis showed that the use of the cooperative jigsaw guided inquiry learning model and initial achievement abilities had a significant effect on students' science process skills. No interaction was found between the learning model and students' achievement abilities on the science process skills of junior high school students in Banda Aceh.